2019
DOI: 10.2967/jnumed.119.231654
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of 18F-DCFPyL PET/CT in Biochemically Recurrent Prostate Cancer in an Academic Center: A Focus on Disease Localization and Changes in Management

Abstract: 18 F-DCFPyL (2-(3-{1-carboxy-5-[(6-18 F-fluoropyridine-3-carbonyl)amino]-pentyl}-ureido)-pentanedioic acid) is a promising PET radiopharmaceutical targeting prostate-specific membrane antigen (PSMA). We present our experience with this single-academic-center prospective study evaluating the positivity rate of 18 F-DCFPyL PET/CT in patients with biochemical recurrence (BCR) of prostate cancer (PC). Methods: We prospectively enrolled 72 men (52-91 y old; mean ± SD, 71.5 ± 7.2) with BCR after primary definitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 26 publications
0
50
0
2
Order By: Relevance
“…Ultimately 16 studies were included in the review (Tab. 2; [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]). Twelve studies reported outcomes using [ 68 Ga]-PSMA-11 PET, while four studies reported data on other PSMA-tracers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately 16 studies were included in the review (Tab. 2; [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]). Twelve studies reported outcomes using [ 68 Ga]-PSMA-11 PET, while four studies reported data on other PSMA-tracers.…”
Section: Resultsmentioning
confidence: 99%
“…A similar study by Song et al used the promising 18 F-labelled tracer 18 F-DCFPyL. They reported change of management in 43/72 patients (60%) in a heterogenous population of patients after RP and radiation therapy with BCR [35]. A study by Schmidt-Hegeman et al primarily investigated the effect of [ 68 Ga]-PSMA-11 PET/CT guided radiation therapy on the biochemical recurrence free survival.…”
Section: Houten 2020mentioning
confidence: 99%
“…Multiple studies have con rmed a high detection rate of recurrent PCa with various PSMA-targeting radiotracers even in biochemical recurrence patients with low PSA levels, and usually exceeds mpMRI (27)(28)(29). Some studies suggest a strong correlation between PSA levels and diagnostic performance of PSMA-targeting PET tracers (27)(28)(29)(30)(31). Our small sample size cohort did not allow for such a correlation, however in a future study with a larger cohort, imaging results should be correlated with PSA levels to test whether this holds true in patients who have undergone brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have con rmed a high detection rate of recurrent PCa with various PSMA-targeting radiotracers even in biochemical recurrence patients with low PSA levels, and usually exceeds mpMRI (28)(29)(30). Some studies suggest a strong correlation between PSA levels and diagnostic performance of PSMA-targeting PET tracers (28)(29)(30)(31)(32). Our small sample size cohort did not allow for such a correlation, however in a future study with a larger cohort, imaging results should be correlated with PSA levels to test whether this holds true in patients who have undergone brachytherapy.…”
Section: Discussionmentioning
confidence: 99%